The U-isotopes modeling in aquifers from Pocos de Caldas plateau, Brazil - Bonotto, Daniel Marcos [UNESP] (Springer, 2005)
U-modeled groundwater residence times were estimated by changes in U-234/U-238 activity ratio (AR) and U content of groundwaters from Pocos de Caldas city situated at the Pocos de Caldas alkaline massif, Brazil. The estimated ages are more realistic than others generated by the use of hydraulic conductivity data and available information about the weathering rate of rocks in the plateau. The U-234/U-238 AR and reciprocal of the dissolved U-content data also defined a ternary plot that allowed the calculation of the relative volume of three source waters for the mixed water. Such U-isotopes modeling for mixing calculations indicated that the dominant phase (68%) in the mixture is thermal.
Keywords: uranium isotopes; groundwater; age and mixing; Pocos de Caldas plateau; Brazil